Pendampingan Pengelolaan Industri Rumah Tangga Bayu Handicraft Menggunakan Website - I Made Pasek Pradnyana Wijaya; Luh Putu Safitri Pratiwi; Ngakan Putu Rio Wiswambara; Ni Luh Gede Kompyang Denia Pradnya Sulasih (BADAN PENERBIT STIEPARI PRESS, 2025)
Bayu Handicraft, owned by Mr. I Wayan Jaya, is a home-based industry (IRT) that produces souvenirs made from marine driftwood waste. In managing his growing business, the partner has not yet implemented any inventory management system and has not promoted his products through online media. When producing souvenirs, the partner sometimes forgets the quantity of stock on hand as well as the details of customers and their orders. The purpose of this community service activity is to assist the partner in developing his business by creating a website that includes features for inventory and order management, which can also be used to promote his business. Guidance and training on how to use the developed website are also provided to help the partner understand how to operate it effectively. As a result of this community service activity, the partner is now better supported in managing his business through the development of the Bayu Handicraft website. The activity was carried out successfully and met the intended objectives.